Smoking Cessation Beliefs Among Saudi University Students in Qassim Region, Saudi Arabia - Almogbel Y (Dove Medical Press, 2020)
Yasser Almogbel Department of Pharmacy Practice, College of Pharmacy, Qassim University, Buraidah, Qassim 51452, Saudi ArabiaCorrespondence: Yasser Almogbel P. O. Box 6800, Department of Pharmacy PracticeCollege of Pharmacy, Qassim University, Buraidah, Qassim 51452, Saudi ArabiaTel +966 16 3014601Email y.almogbel@qu.edu.saIntroduction: Despite Saudi officials initiating a variety of smoking cessation programs, smoking in the country has not decreased. Thus, the objective of this study was to identify the factors associated with Saudi students’ beliefs about available smoking cessation interventions.Methods: A cross-sectional, pre-tested, and validated paper-based survey was administered to a cohort from a university in the Qassim region. Bivariate analyses and logistic regression were conducted to explore the factors associated with the students’ beliefs regarding behavioral and pharmacotherapy interventions for smoking cessation.Results: Out of 1158 surveys distributed, 958 responses were received (82.7% response rate). Students aged > 23 years were more likely to believe in a behavioral intervention (marginal effect = 10.4%; 95% CI, 2.3%– 18.6%). However, the respondents who indicated that they had smoked a hookah over the past 30 days were less likely to believe in either the pharmacotherapeutic (marginal effect = -7.9%; 95% CI, − 15.6 to − 0.3%) or the behavioral (marginal effect = -8.1%; 95% CI, − 16.2% to − 0.1%) interventions. Students who believed that the hookah was the same as or less harmful than cigarettes (marginal effect = − 25.6%; 95% CI, − 34.7% to − 16.6%) and (marginal effect = − 12.3%; 95% CI, − 22.3% to − 2.3%), respectively, were less likely to believe in pharmacotherapeutic interventions. Multiple logistic regression analyses found that hookah smokers with a willingness to quit smoking were more likely to believe in the effectiveness of cessation medications (marginal effect =  42.9%; 95% CI, 28.2%– 57.6%) and behavioral interventions (marginal effect =  28.6%; 95% CI, 9.3%– 48.0%).Conclusion: This study found that smoking a hookah and its harmfulness were negatively associated with smoking cessation medications interventions. Regarding beliefs about behavioral interventions, while age was positively associated, hookah smoking and its harmfulness had a negative association. Willingness to quit smoking was positively associated with both medication and behavioral interventions.Keywords: behavior, college students, Kingdom of Saudi Arabia, quitting smoking, utilization of services